A prospective study on evaluation of antibiotics usage in patients with sepsis at a tertiary care hospital - Vanlalpeka, H. S.; K. George, Blessy; Ramaiah, Balakeshwa (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Most developing countries are adopting antibiotic usage in sepsis. This study was conducted to evaluate the antibiotic usage in patients and to study medical adherence in high-risk patients. The study in particular aims to evaluate antibiotic usage in sepsis patients along with their related ADR’s. The study also aims to optimize the usage of antibiotics in high-risk patients at a tertiary care hospital. Methods: Study was prospective and observational review of patients record in the hospital. Clinical notes, medication chart and electronic data management system at the hospital were used to analyse usage of antibiotics. Culture and sensitivity reports were obtained from relevant departments. Observations were then compiled and documented. Results: Out of 40 cases collected 22 (55%) patients were male and 18 (45%) were female. Majority of the study population belongs to 71 years and above with 15 (37.5%) followed by age group of 41-60 years with 14 (35%). Most frequently prescribed antibiotics were found to be meropenem 16 (21.33%) and piperacillin tazobactam 14 (18.67%). The most resistant antibiotic was found to be cotrimazole in 35 (87.5%). ADRs were found in 35% of all cases. Conclusions: Prescribing patterns for antibiotics need to be optimized. Adherence to and update of the policy is also recommended. It was found that the adherence to hospital antibiotic policy is low.